[Bristle worms (Annulata Chaetopoda) Bay of Sebastopol] [Original] Щетинконогие черви (Annulata Chaetopoda) Севастопольской бухты - Bobretzky, N. (Verhandlunger der Naturforschender Versammlung, St.Petersburg, Ser. Zoologie [also Russian journal title: Труды 1-го съезда русских естествоиспытателей в Санкт-Петербурге, Отдел зоологии (Proceedings of the 1st Congress of Russian Naturalists in St. Petersburg, Department of Zoology)], 1868)
none. Species included are: Sigalium ocellatum n.sp. p.140 (fig. 1-5) Lysidice ninetta Audouin & Edwards, p.142 (fig 6–12) Heteronereis maculata n.sp. p.144 (fig. 13-22) Heteronerels crenaticirra n.sp. p.147 (fig. 23-30) Heteronereis bipartita n.sp. p.148 (fig. 31-36) Phyllodoce tuberculata n.sp. p.150 (fig. 37-40) Eulalia virens Ehlers, p.152 Eulalia flavescens n. sp. p.153 (fig. 41-43). Eteone striata n.sp. p.154 (fig. 44-46) Cirratulus cincinnatus n.sp. p.155 (fig. 47-49) Terebellides (Corephorus) carnea n.sp. p.156 (fig. 50-52) Polycirrus jubatus n.sp. p.158 (fig. 53-54)
World Polychaeta Database (WPolyDb). A generic location for Sebastopol Bay is 44.6222° 33.5209°